An Analysis of Laboratory Characteristics of Patients with Suspected Rheumatoid Arthritis - İhsan Hakkı ÇİFTCİ,; Gülşah AŞIK,; Hasan TOKTAŞ,; Davut ÇUFALI,; Ümit DÜNDAR,; Engin KARAKEÇE1, (Archives of Rheumatology, 2013)
Objectives: The aim of this study was to characterize a population of patients with rheumatological signs and symptoms according to laboratory tests. Patients and methods: Data of a total of 386 patients (90 males, 296 females; mean age 45.9 years; range 14 to 91) with rheumatological signs and symptoms for a three-year period were retrospectively analyzed. Inflammatory activity using erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) tests were evaluated at the microbiology laboratory of Afyon Kocatepe University, Faculty of Medicine, Afyonkarahisar. The presence of rheumatoid factor (RF) and cyclic citrullinated peptide (CCP) antibodies were also analyzed. The ESR (mm/h) was determined by standard methods, while the RF and CRP were measured by immunonephelometry. The anti-CCP was studied by using a test kit according to the manufacturer's instructions. Results: A total of 270 patients were examined in a physical medicine and rehabilitation clinic. The results for anti-CCP, RF, CRP, and ESR were positive in 58 (21.5%), 77 (28.9%), 120 (44.4%) and 107 patients (39.6%) respectively. Among these patients, a total of 67 were diagnosed with rheumatoid arthritis (RA). When we considered the association of ESR, CRP, RF, and anti-CCP positivity with RA diagnosis, both anti-CCP (F=0.920) and RF (F=0.782) had a high positive correlation with RA. There was a close association between CRP (F=0.289) and ESR (F=0.236). Each of them had a moderate correlation with RA. Conclusion: Our study results showed that anti-CCP, followed by RF was the most closely associated autoantibody in suspected RA patients. The anti-CCP and RF combination provided the best test sensitivity.